Pengaruh Motivasi Kerja Dan Organizational Citizenship Behavior (OCB) Terhadap Kinerja Pegawai (Studi Kasus Pada Aparatur Sipil Negara Dinas Kesehatan Kota Tasikmalaya) (International Forum of Researchers and Lecturers, 2023)
This study aims to determine the simultaneous and partial effect of Work Motivation and Organizational Citizenship Behavior (OCB) on Employee Performance in the State Civil Apparatus of the Tasikmalaya City Health Service. The research method used in this study is to use quantitative research methods with descriptive methods. Respondents in this study were civil servant employees at the Tasikmalaya City Health Office as many as 90 employees. The type of data used in this study is primary data obtained through questionnaires. The data testing technique used in this study uses the validity test, reliability test and classic assumption test. Data analysis in this study used multiple regression analysis using SPSS software version 25. Data collection techniques used library research, interviews, and questionnaires. The results of the study show that work motivation and organizational citizenship behavior (OCB) simultaneously have a significant effect on employee performance. Work motivation partially has a significant effect on employee performance. Organizational Citizenship Behavior (OCB) partially has a significant effect on Employee Performance.